Reduction of differential equations and conditional symmetry - Zhdanov, R. Z.; Tsifra, I. M.; Жданов, Р. З.; Цифра, І. М. (Institute of Mathematics, NAS of Ukraine, 1996)
We determine conditions under which partial differential equations are reducible to equations with a smaller number of independent variables and show that these conditions are necessary and sufficient in the case of a single dependent variable.